Pengaruh Pembiayaan Dan Efisiensi Operasi Terhadap Pencapaian Laba Pada BPR Syariah Di Jawa Timur - Hanif, Rifki; Fitri, Raisa (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
This study aims to determine the effect of Operating Costs and Income and Loan Asset Ratio to Achievement of Profit in Islamic Rural Banks in East Java. The existence of Sharia Banking is increasingly recognized by the government as shown by the increasing number of banks conducting business based on sharia principles in 2011. In 2011, banking performance showed positive growth supported by high profitability, and other financial indicators that showed positive growth , where growth in 2011 is relatively higher. Total assets of BPRS increased by 28.21% from Rp. 2.73 trillion (2010) to Rp. 3.50 trillion (in 2011), (Bank Indonesia, 2011). This study uses multiple regression analysis model. And the type of data used is secondary data taken through Bank Indonesia Report.